Gas purification - Kohl, Arthur L.; Nielsen, Richard (Richard B.) (Houston, Tex. : Gulf Pub., 1997)
This massively updated and expanded fifth edition is the most complete, authoritative engineering treatment of the dehydration and gas purification processes used in industry today. Of great value to design and operations engineers, it gives practical process and equipment design descriptions, basic data, plant performance results, and other detailed information on gas purification processes and hardware. This latest edition incorporates all significant advances in the field since 1985. You will find major new chapters on the rapidly expanding technologies of nitrogen oxide control, with discussions of regulatory requirements and available processes; absorption in physical solvents, covering single component and mixed solvent systems; and membrane permeation, with emphasis on the gas purification applications of membrane units. In addition, new sections cover areas of strong current interest, particularly liquid hydrocarbon treating, Claus plant tail gas treating, thermal oxidation of volatile organic compounds, and sulfur scavenging processes. This volume brings you expanded coverage of alkanolamines for hydrogen sulfide and carbon dioxide removal, the removal and use of ammonia in gas purification, the use of alkaline salt solutions for acid gas removal, and the use of water to absorb gas impurities. The basic technologies and all significant advances in the following areas are thoroughly described: sulfur dioxide removal and recovery processes, processes for converting hydrogen sulfide to sulfur, liquid phase oxidation processes for hydrogen sulfide removal, the absorption of water vapor by dehydrating solutions, gas dehydration and purification by adsorption, and the catalytic and thermal conversion of gas impurities.
Introduction. Alkanolamines for Hydrogen Sulfide and Carbon Dioxide Removal. Mechanical Design and Operation of Alkanolamine Plants. Removal and Use of Ammonia in Gas Purification. Alkaline Salt Solutions for Acid Gas Removal. Water as an Absorbent for Gas Impurities. Sulfur Dioxide Removal. Sulfur Recovery Processes. Liquid Phase Oxidation Processes for Hydrogen Sulfide Removal. Control of Nitrogen Oxides. Absorption of Water Vapor by Dehydrating Solutions. Gas Dehydration and Purification by Adsorption. Thermal and Catalytic Conversion of Gas Impurities. Physical Solvents for Acid Gas Removal. Membrane Permeation Processes. Miscellaneous Gas Purification Techniques. Index.
Includes bibliographical references and index.
Keywords: Gases -- Purification; Electronic books